PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA VIERA OLEH-OLEH KOTA PEKANBARU - Febrianza Fadhilla; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Consumer satisfaction is one of the most important factors in the marketing concept, this is what lies behind this research. Good product quality, appropriate pricing in front of consumers is the most important part of supporting factors for customer satisfaction. This strategy is implemented by Viera Souvenir Pekanbaru. This study aims to determine the effect of product quality, pricing on consumer satisfaction at Viera By-Oleh Pekanbaru City. The method used in this research is descriptive and quantitative, with data sources from primary data and secondary data. The analytical method used in this research is simple and multiple linear regression analysis, and through validity and reliability tests. In this study the results obtained are that Product Quality (X1) has a positive and significant effect on Consumer Satisfaction (Y), Price Fixing (X2) has a positive and significant effect on Consumer Satisfaction (Y), and Product Quality (X1), Pricing ( X2), simultaneously has a positive and significant effect on Consumer Satisfaction (Y) at Viera Souvenirs, Pekanbaru City.Keywords: Product Quality, Pricing, Customer Satisfaction